Стохастическая регуляризация обратной задачи - Лисиченко, Г.В.; Забулонов, Ю.Л.; Ревунова, Е.Г.; Буртняк, В.М. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2009)
The mathematical method of decision of task of increase of exactness of localization of prostranstvenno-raspredelennykh sources of radiation contamination and renewal of parameters of function of superficial closeness of gamma-radiation is offered. Comparing of this method is conducted to existing on a criterion errorlevel of renewal.